Large-Scale Synthesis of Piperazine-2,6-dione and Its Use in the Synthesis of Dexrazoxane Analogues - Roh, Jaroslav; Karabanovich, Galina; Novakova, Veronika; Šimůnek, Tomáš; Vávrová, Kateřina (Synthesis, 2016)
An efficient, large-scale synthesis of piperazine-2,6-dione was developed. The advantages of this procedure include the use of inexpensive starting materials, satisfactory yields, and a convenient workup without the need for chromatographic techniques. Furthermore, this procedure can be easily modified for the preparation of 1-substituted piperazine-2,6-dione hydrobromides. The utility of the prepared piperazine-2,6-dione was demonstrated in the synthesis of a novel analogue of the only drug used in clinical practice to prevent anthracycline-induced cardiotoxicity, dexrazoxane.
Keywords: piperazine-2,6-dione; large-scale synthesis; dexrazoxane; cyclization; synthesis; formamide